Unraveling the molecular landscape of lead-induced cochlear synaptopathy: a quantitative proteomics analysis - Bhatia, Pankaj; Mehmood, Shomaila; Doyon-Reale, Nicole; Rosati, Rita; Stemmer, Paul M.; Jamesdaniel, Samson (Frontiers in Cellular Neuroscience, 2024)
Exposure to heavy metal lead can cause serious health effects such as developmental neurotoxicity in infants, cognitive impairment in children, and cardiovascular and nephrotoxic effects in adults. Hearing loss is one of the toxic effects induced by exposure to lead. Previous studies demonstrated that exposure to lead causes oxidative stress in the cochlea and disrupts ribbon synapses in the inner hair cells. This study investigated the underlying mechanism by evaluating the changes in the abundance of cochlear synaptosomal proteins that accompany leadinduced cochlear synaptopathy and hearing loss in mice. Young-adult CBA/J mice were given lead acetate in drinking water for 28 days. Lead exposure significantly increased the hearing thresholds, particularly at the higher frequencies in both male and female mice, but it did not affect the activity of outer hair cells or induce hair cell loss. However, lead exposure decreased wave-I amplitude, suggesting lead-induced cochlear synaptopathy. In agreement, colocalization of pre-and postsynaptic markers indicated that lead exposure decreased the number of paired synapses in the basal turn of the cochlea. Proteomics analysis indicated that lead exposure increased the abundance of 352 synaptic proteins and decreased the abundance of 394 synaptic proteins in the cochlea.Bioinformatics analysis indicated that proteins that change in abundance are highly enriched in the synaptic vesicle cycle pathway. Together, these results suggest that outer hair cells are not the primary target in lead-induced ototoxicity, that lead-induced cochlear synaptopathy is more pronounced in the basal turn of the cochlea, and that synaptic vesicle cycle signaling potentially plays a critical role in lead-induced cochlear synaptopathy.